Skin Grafts - Gore, Madhuri (IntechOpen, 2013)
Split thickness skin grafting procedure is a simple but essential and important one to achieve closure of a full thickness or deep partial thickness skin defect. It needs to be performed with care and precision for successful outcome. The present publication is devoted to skin grafts. Three important components of this procedure are preparation of wound bed, fixation of skin grafts to the recipient area to improve possibility of graft take and management of skin graft donor area for both full thickness and split thickness grafts. The chapters have been distributed in these three sections.